WASTE PRODUCT OF GROWING THE GENUS ECHINACEA (ECHINACEA MOENCH) AS PROMISING SOURCE OF BIOLOGICALLY ACTIVE SUBSTANCES - Мединець, О. Е. (Scientific Progress & Innovations, 2013)
It is determined the dependence of winter wheat affection by brown rust to time of plants’ spring revegetation (TSRV) and to periodicity of solar activity on 55-years observations Myrgorod selection field of Poltava region. Time of spring revegetation is a complex index for following light, thermal and partially water conditions of plants’ spring development, that winter. Maximum sowing affection by brown rust was observed in years with average solar activity (61-120 W) under optimum and late time of spring revegetation. Minimum affection that doesn’t demand protection agents application was observed in combining of two factors: 1 – in years with early time of spring revegetation (till 20th of March) and not depending on solar activity and 2 – in years with high solar activity (121-190W) and light dependence from time of spring revegetation. Such years were 28 between 55. Obtained results can be used in prediction of brown rust development on winter wheat.